Dental Journalism: Finding Fact, Fiction, Fallacies, Fraud… (Orthodontic Journal of Nepal, 2015)
According to an opinion poll doctors topped the list among various professionals whom the public believe the most in telling truth; while journalists were on the bottom of the list. The MORI poll carried on behalf of British Medical Association showed that 87% believe doctors don’t lie, while 85% assume journalists don’t report truth. Surfacing amidst the trust bestowed upon the doctors and mistrust for the journalists, this article attempts to explain various aspects of dental journalism.